Effect of low-intensity pulsed ultrasound therapy on a fibroblasts cell culture (Fisioterapia e Pesquisa, 2015)
Within the physiotherapy practice there is a wide use of therapeutic ultrasound for the treatment of various musculoskeletal disorders. The aim of this study was to evaluate the effect of Low Intensity Ultrasonic irradiation with differents forms of pulse and intensity in cell culture of L929 fibroblasts (ATCC CCL-1 NCTC), in order to check cell viability and define parameters of dosimetry. For this purpose, it was used the application of pulsed ultrasound with a frequency of 1MHz in cultured fibroblast cells divided into five groups (control and instantaneous intensity of 0.3W/cm2-10%, 0.3W/cm2 -20%, 0.5W/cm2-10% and US 0.5W/cm2-20% - 100Hz). Irradiation occurred at intervals of 24, 48 and 72 hours for two minutes and 24 hours after each irradiation test MTT [3-(4,5-dimethylthiazol)-2,5-diphenyltetrazolium bromide] was performed. Results showed that when comparing the values of viable cells by MTT method in the five groups, we could not find statistically significant difference in any of them, in these three conditions (24, 48 and 72 hours); while. Whereas, when performing the analysis of repeated measures in the different groups, it was found a statistically significant difference only in the group irradiated with ultrasound at 0.5W/cm2 with pulse regime of 10% (p=0.003). Based on these results, it is concluded that the Low Intensity Ultrasonic irradiation in L929 fibroblast cell culture, only in the group with an intensity of 0.5W/cm2 -10% obtained numerical growth, with statistical significance in all periods evaluation.